THE INFLUENCE OF BRANDING AND PRICE ON PURCHASE DECISIONS OF SKINCARE PRODUCTS - Frans Sudirjo; Rachmadi Indrapraja; Ilham Arief; La Mema Parandy; Siti Nuridah (Sean Institute, 2023)
The purpose of this study is to ascertain the impact of pricing and branding on skincare purchase decisions. This research employs a quantitative methodology. There were 200 participants in this study, all of them were students. The sample is used through random sampling, which groups the adjusted ages. In this investigation, 150 samples were used. strategies for gathering data for research using a questionnaire. According to the data analysis's findings, branding and price have a considerable, simultaneous, and partial influence on consumers' decisions to buy skincare. As can be observed, the findings of the study's partial t test indicate that branding has a significance of 0.000. The t-count obtained is higher than the t-table value, which is 1.978, when compared to it. Additionally, a significant value of 0.000 was found for the price significance results for skincare choices. The t-count obtained is higher than the t-table value, which is 1.978, when compared to it. 60% is indicated by the coefficient of determination, or R square, of 0.60.